Circulating microRNA‐1246 as a possible biomarker for early tumor recurrence of hepatocellular carcinoma. Issue 7 (23rd May 2019) - Chuma, Makoto; Toyoda, Hidenori; Matsuzaki, Juntaro; Saito, Yoshimasa; Kumada, Takashi; Tada, Toshifumi; Kaneoka, Yuji; Maeda, Atsuyuki; Yokoo, Hideki; Ogawa, Koji; Kamiyama, Toshiya; Taketomi, Akinobu; et al.
Abstract : Aims: Early tumor recurrence (ETR) after hepatic resection is a crucial predictor of poor prognosis in patients with hepatocellular carcinoma (HCC). The aim of this study was to identify clinically significant serum microRNAs (miRNAs) involved in the ETR of HCC. Methods: We compared expression profiles of circulating miRNAs from serum samples between five HCC patients with ETR (recurrence within 12 months after hepatectomy) and five HCC patients without recurrence using microarray analysis of miRNA. The identified miRNA associated with ETR was further verified in 121 HCC patients, 73 liver disease patients, and 15 health controls by real‐time quantitative reverse transcription–polymerase chain reaction (PCR). Results: Of the approximately 2000 miRNAs analyzed, we identified 15 miRNAs for which expression levels correlated significantly with ETR. Of these miRNAs, we further investigated expression of miRNA‐1246 (miR‐1246). Quantitative PCR confirmed that miR‐1246 was upregulated in HCC with ETR, compared to the level in HCC without ETR ( P  < 0.001). Serum miR‐1246 showed a receiver operating characteristic curve area of 0.762, with 77.4% specificity and 54.1% sensitivity in discriminating HCC patients with ETR from HCC patients without ETR. Altered expression of miR‐1246 was associated with aggressive tumor characteristics, including tumor–node–metastasis classification ( P  = 0.0413), tumor differentiation ( P  = 0.0419), and portal vein invasion ( P  = 0.0394). Moreover, multivariate Cox regression analysis identified serum miR‐1246 level as an independent risk factor for overall survival (hazard ratio, 2.784; 95% confidence interval, 1.528–5.071; P  = 0.0008). Conclusion: Circulating miR‐1246 in serum has strong potential as a novel ETR and prognostic biomarker for HCC.